War, transparency and control: the military architecture of operational warfare. Issue 3 (2nd July 2016) - Öberg, Dan
Abstract: In contemporary research, transparency is commonly understood to indicate and guarantee openness, in ways that make it synonymous with positive characteristics of governing. However, the allegedly benevolent link between transparency and governing has also been questioned, giving rise to arguments that transparency enables violent social control. Drawing upon this latter view, the article stages an encounter between critical debates on transparency and critical accounts of war to examine the way that they come together in the operationalization of warfare. Engaging particularly with Jean Baudrillard's writing on transparency, the article inquires into the way control is socially manufactured and administered through military doctrines. It concludes that the operationalization of warfare is not, as many tend to argue, first and foremost about a response to practical problems when conducting wars. Rather, it consists of the potential to unveil global space and global time as an attempt to maintain and control future political becoming.